Retratos do eu: as identidades metaforizadas de aprendizes universitários de inglês em Hong Kong e no Brasil - Ronaldo Corrêa Gomes Júnior (2015)
If metaphors are a cognitive phenomenon by which we make sense of the world and ourselves (LAKOFF AND JOHNSON, 1980); understanding identities and how they are constructed can also be a matter of metaphor. This research aims at investigating the metaphorical identitites of English students of the Federal University of Minas Gerais and the University ofHong Kong by examining the metaphors in language learning histories (LLH). These narratives were written in a multimodal way, that is, using text, images, sounds, videos etc. In this qualitative and interpretivist study, two LLH database will be analyzed - one from each university. The data analysis consisted on of the following steps: first, all significantmetaphorical units were highlighted; second, after repeated readings, metaphors were grouped in categories according to their regularities; third, it was analyzed how the selves were discursively and metaphorically constructed; and finally, the identity profiles of each database were traced. The data reveal that the most frequent metaphorized identities in both group of participants are the ones which involve journeys and paths, such as the traveller. In the HongKong data, other metaphorized identities involve intense action, such as the constructor and soldier. In the Brazilian data, the other most frequent metaphorized identites are related to reading. Another conclusion is that the multiplicity of identities does not imply their fragmentation. Thus, the blended identities notion is proposed. Getting to know the metaphorsstudents use to talk about language learning can help teachers better understand the identities that are constructed during the process; what can affect both teaching and learning. One of the main contributions of this research is also the association of cognitive and social theories,understanding learners as sociocognitive beings who are influenced by social, embodied, kinesthetic, and identity experiences.